ANALISIS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN WONOSOBO - Dewi, Miranda; Nilasari, Ayunda Purti (Transpublika Publisher, 2022)
This study aims to analyze the financial statements of the local government of Wonosobo Regency. This study uses a descriptive method with a qualitative approach. The results of the ratio analysis using the Wonosobo Regency report data that have been described previously, it can be concluded that the conclusion of the Wonosobo Regency government's financial performance in 2018-2019 if seen from the regional financial independence ratio can still be categorized as very low. In addition, the financial performance of the Wonosobo Regency government in 2018-2019 when viewed based on the effectiveness ratio is categorized as very effective. Meanwhile, in the analysis of the operational expenditure compatibility ratio data in 2017-2018 it can be said that the Wonosobo Regency government has a tendency to use its budget for operational expenditure.